The food and financial crises in Sub-Saharan Africa: origins, impacts and policy implications - Lee, David R.; Ndulo, Muna B. (CAB International, 2011)
Dramatic increases in food prices, as witnessed on a global scale in recent years, threaten the food security of hundreds of millions of the rural poor in Sub-Saharan Africa alone. This book focuses on recent food and financial crises as they have affected Africa, illustrating the problems using country case studies, that cover their origins, effects on agriculture and rural poverty, their underlying factors and making recommendations as to how such crises could best be addressed in the future.